Prevalence and Factors Associated With Delayed Puberty Among Adolescents on Boosted Protease Inhibitor–based Second-line Antiretroviral Therapy: A Cross-sectional Study at a Pediatric Infectious Diseases Clinic in Uganda. Issue 5 (22nd February 2023) - Nakiddu, Nana Jacqueline; Bakeera-Kitaka, Sabrina; Musoke, Philippa
Abstract : Background: Delayed puberty is a recognized phenomenon among children living with HIV type 1 infection but has not been widely reported among adolescents on second-line or newer treatments in high burden settings. The study aimed to determine the prevalence of, and factors associated with delayed puberty among adolescents on boosted protease inhibitor-based second-line antiretroviral therapy (ART) in Uganda. Methods: Between December 2017 and May 2018, we conducted a cross-sectional study among adolescents living with HIV (ALWHIV) 10–19 years of age on atazanavir- and lopinavir-based regimens at the Paediatric Infectious Diseases Clinic, Kampala. Participants were on ART for at least 3 months and had a recent viral load. Sociodemographics, clinical measurements: body mass index for age Z score, height for age Z score, Tanner staging were collected. ART history was extracted from medical records. The outcome was delayed puberty defined as absence of signs of breast development in a girl 13 years of age or a testicular volume of less than 4 mL in a boy 14 years of age by Tanner staging, or an age for Tanner staging which was at least 2 standard deviations above the expected mean. Results: Among 230 perinatally infected ALWHIV participants, 14.7 ± 3.1 years of age were included, 54.9% were female, 5.2% were wasted and the median duration on ART was 9.5 years (interquartile range 7.3–11.7). The prevalence of delayed puberty was 8.7% (10.4% females, 6.7% males). Overall mean age estimates at different Tanner stages by sex were significantly higher than reference populations. Age at ART initiation (adjusted odds ratio 1.37, 95% confidence interval: 1.06–1.77) and body mass index for age Z score (adjusted odds ratio: 7.63, 95% confidence interval: 1.80–32.38) were associated with delayed puberty. Conclusions: Timely initiation of ART and nutritional monitoring could optimize body weight and consequently, normal puberty for ALWHIV. Longitudinal studies could establish biological diagnoses and guide treatment of delayed puberty in this population.